O IMC dos agentes de controle de zoonoses do município de Uberlândia e sua influência nas atividades laborais - Roscia, Americo (2019)
The objective of this study with the Zoonoses Control Agents of the Department of Health of the city of Uberlândia-MG was to determine and classify body mass index (BMI), waist / hip ratio (WHR), blood pressure (BP) and other parameters of bioimpedance, as well as to analyze the socio-demographic profile of this population, in order to verify if this body mass index and bioimpedance results plus the lifestyle of the same, could influence the potentialization of the ergonomic risks and the indicators of this research group. Among the non-communicable chronic diseases (NCD), 2.5% of individuals with Diabetes, 4.9% with High Cholesterol and 4.9% High Blood Pressure were surveyed, 0.8% of Cancer, and 2.5% with Cardiac and/or Circulatory Diseases and when compared with the other data evaluated as the Systolic/Diastolic Pressure of the Female group that presented a total of 43.1% of this group with Hypertension problems against 40.8% of the Male group, and with the evaluation of the answers to the questionnaire where in the question of the places where they presented pain, it was verified that 36.9% was of Pain of the Column; 10.9% of the Arms and Shoulders and 11.5% of Legs and Feet, which are usually associated with obesity, we can observe a great risk for the propensity of heart and vascular diseases, mainly because 56% are in the group of smokers, and 72.9% "very rarely", "sometimes" or "never", practice physical activities and with it all being aggravated by the work activity itself where the risk of accidents physical and ergonomic factors are inherent to the function itself, a considerable relationship of these factors is concluded with a potentiation not only of the CNCDs present, but also of the potentialisation of the risks of the occurrence of new diseases, as well as a greater potentialisation of the risks of accidents of work, including physical and ergonomic risks, present in their work activities, where they walk for long periods, climb stairs, walk on rooftops, carry a substantial weight, and collect used tires s and materials that can propagate the proliferation of Dengue, are part of these activities.